QT interval variability and heart rate turbulence are associated with clinical characteristics in congenital heart disease patients with a systemic right ventricle - Zandstra, Tjitske; Kiès, Philippine; Man, Sum-Che; Maan, Arie; Bootsma, Marianne; Vliegen, Hubert; Egorova, Anastasia; Holman, Eduard; Schalij, Martin; Jongbloed, Monique (Journal of cardiology, 2020)
•QT interval variability and heart rate turbulence reflect autonomic function.•In patients with a systemic right ventricle, these measures:•Correlated with medication use and with tachy-arrhythmias.•Heart rate turbulence was independently associated with clinical events. QT interval variability (QTV) and heart rate turbulence (HRT) are measures of cardiac autonomic function, which, when abnormal, are correlated with ventricular arrhythmias and worse clinical outcome. This study aims to evaluate QTV and HRT in patients with a systemic right ventricle (RV) and to assess correlations with clinical characteristics. In a retrospective cohort study, QTV and HRT were derived from 24-h Holter registrations of patients with a systemic RV and healthy controls. QTV and HRT were compared between groups. In patients, the association between QTV, HRT, and clinical characteristics was assessed. Holter recordings from 40 patients (mean age 40 years, 16 females) and 37 healthy controls (mean age 42 years, 21 females) were analyzed. Groups were comparable in terms of age and sex. QTV was increased in patients compared with controls (p < 0.001), HRT did not differ significantly between the groups. Increased QTV and decreased HRT correlated with medication use, especially of diuretics, and with clinical events, particularly supraventricular arrhythmias. Increased QTV correlated with reduced systemic RV function. Decreased HRT was independently associated with a larger number of past clinical events (estimate −0.33, 95% CI −0.63 to −0.02, p = 0.037). QTV was higher in women in both patients and controls (p = 0.041 and p = 0.034, respectively). QTV and HRT are associated with clinical factors and events in patients with a systemic RV. Further studies are mandatory to confirm their prognostic value.